Exosome-derived proteins in gastric cancer progression, drug resistance, and immune response - Jiayu Wang; Huan Zhang; Juntao Li; Xiangyu Ni; Wenying Yan; Yueqiu Chen; Tongguo Shi (Cellular & Molecular Biology Letters)
Abstract Gastric cancer (GC) represents a prevalent malignancy globally, often diagnosed at advanced stages owing to subtle early symptoms, resulting in a poor prognosis. Exosomes are extracellular nano-sized vesicles and are secreted by various cells. Mounting evidence indicates that exosomes contain a wide range of molecules, such as DNA, RNA, lipids, and proteins, and play crucial roles in multiple cancers including GC. Recently, with the rapid development of mass spectrometry-based detection technology, researchers have paid increasing attention to exosomal cargo proteins. In this review, we discussed the origin of exosomes and the diagnostic and prognostic roles of exosomal proteins in GC. Moreover, we summarized the biological functions of exosomal proteins in GC processes, such as proliferation, metastasis, drug resistance, stemness, immune response, angiogenesis, and traditional Chinese medicine therapy. In summary, this review synthesizes current advancements in exosomal proteins associated with GC, offering insights that could pave the way for novel diagnostic and therapeutic strategies for GC in the foreseeable future.